(untitled) (Italiano LinguaDue, 2023)
In language teaching, especially in European multilingual and multicultural contexts, mediation has become an essential tool aimed at reducing the distance between two (or more) linguacultural dimensions. Mediation is a notion officially introduced by the Council of Europe’s Common European Framework of Reference (2001), and further developed in the current Companion Volume (2020), where mediation strategies and activities acquire a crucial role as a new form of managing the interaction in the language classroom as well as in daily communicative situations. Mediation is here presented as fundamental in cross-cultural communication and recommended as indispensable in plurilingual educational contexts. In this perspective, mediation and mediation strategies are central in multilingual educational and professional contexts where native and non-native speakers interact by means of an increasing use of ‘lingua francas’, mainly English as a lingua franca (ELF). The present study aims to illustrate the introduction of different language mediation strategies by means of specific tasks and activities within ELF-aware (Sifakis, Bayyurt, 2018) academic ELT (English Language Teaching) courses for language and cultural mediation and international communication. The research focus is on the emerging real-world ‘hybridization’ processes, adopted as learning tools in ELT practices, which prove to be particularly useful for enhancing learners’ awareness of communicative dynamics and the conscious use of mediation skills and strategies in multicultural settings. Pedagogical implications for language teacher education deriving from this study will be discussed. Introduzione di strategie di mediazione nell’insegnamento della lingua inglese in contesti accademici plurilingui Nell’insegnamento delle lingue, soprattutto in contesti europei multilingue e multiculturali, la mediazione è diventata uno strumento essenziale per ridurre la distanza tra due (o più) dimensioni linguistiche e culturali. La mediazione è una nozione introdotta ufficialmente dal Quadro Comune Europeo di Riferimento del Consiglio d’Europa (2001) e ulteriormente sviluppata nell’attuale Volume complementare (2020), dove le strategie e le attività di mediazione acquisiscono un ruolo cruciale come nuova forma di gestione dell’interazione in classe e nelle situazioni comunicative quotidiane. La mediazione viene qui presentata come fondamentale nella comunicazione interculturale e raccomandata come indispensabile nei contesti educativi plurilingui. In questa prospettiva, la mediazione e le strategie di mediazione sono centrali nei contesti educativi e professionali plurilingui in cui parlanti nativi e non nativi interagiscono attraverso un uso crescente di “lingue franche”, principalmente l’inglese come lingua franca (ELF). Il presente studio si propone di illustrare l’introduzione di diverse strategie di mediazione linguistica attraverso compiti e attività specifiche all’interno di corsi accademici ELT (English Language Teaching) basati sull’ELF (Sifakis, Bayyurt, 2018) per la mediazione linguistica e culturale e la comunicazione internazionale. La ricerca si concentra sui processi di “ibridazione” emergenti nel mondo reale, adottati come strumenti di apprendimento nelle pratiche ELT, che si rivelano particolarmente utili per migliorare la consapevolezza degli studenti delle dinamiche comunicative e l’uso consapevole di abilità e strategie di mediazione in contesti multiculturali. Saranno discusse le implicazioni pedagogiche per la formazione degli insegnanti di lingue derivanti da questo studio.